NanoMuscle: controllable contraction and extension of mechanically interlocked DNA origami. Issue 5 (16th December 2019) - Chao, Yu-Chen; Hong, Yu-Jun; Lee, Chieh-Yu; Zhuang, Shao-Chien; Wu, Meng-Ting; Lee, You-Yi; Lee, Hua-Yun; He, You-Sheng; Yu, Hsing-Yi; Huang, Yang-Zhe; Chern, Edward; Jiang, Hong-Ren
Abstract : NanoMuscle is able to switch between its thermodynamic bistable states, where each state corresponds to NanoMuscle's contracted or extended conformation. Abstract : Artificial molecular machines synthesized in supramolecular chemistry have attracted great interest over the past decades. DNA origami presents an alternative approach to construct nano-machines by directly designing its thermodynamically stable state by DNA sequences. Here, we construct a molecular device, named NanoMuscle, with mechanically interlocked DNA origami. NanoMuscle's configuration – either extended or contracted – can be controlled by adding specific DNA strands. We monitored NanoMuscle's multistep synthesis with gel electrophoresis, and verified that monomers of the NanoMuscle are interlocked at correct orientation with transmission electron microscopy (TEM). We then validated that NanoMuscle can switch between extended and contracted configuration. By converting binding energy from DNA hybridization and Brownian motion to mechanical movements, NanoMuscle may serve as a novel building block for future mesoscale machinery.